Evaluation and comparison of the functional properties of high-fat and low-fat protein- enriched coconut residue flour - Bengo, Geraldine Cabana; Dumelod, Benelyn Domingo (1994.)
The functional properties of high-fat and low-fat PECRF were evaluated and compared. All-purpose flour (APF) was used as the reference material. Procedures for the evaluation of solubility, viscosity, emulsifying capacity, emulsion stability, water absorption, fat absorption, and bulk density were collected. From among those collected the best procedure in terms of reproducibility and consistency of results, availability of equipment and materials needed, rapidity, and cost were selected and standardized using APF as the test material. Results showed that APF was soluble at pH 8-12, while both types of PECRF were soluble at pH 7-12. APF formed the most viscous solution, followed by the low-fat PECRF, and finally the least viscous high-fat PECRF. Among the three flours, APF had the highest emulsifying capacity, while high-fat PECRF had the lowest emulsifying capacity. Intermediate was the low-fat PECRF. The most stable emulsion was formed by the APF, followed by low-fat PECRF. The least stable emulsion was formed by high-fat PECRF. With regard to the water absorption properties of the samples, low-fat PECRF was the most absorptive, followed by high-fat PECRF, and then finally, the least absorptive was the APF. The fat absorption properties of the samples were ranked as follows: low-fat PECRF, most absorptive; APF, second; high-fat PECRF, least absorptive. Finally, the greatest bulk density was exhibited by APF, followed by high-fat PECRF, and the least dense was the low-fat PECRF. In general, low-fat PECRF exhibited better functionality than high-fat PECRF. It will be more advantageous, in terms of functionalit and keeping quality, to utilize low-fat PECRF than high-fat PECRF.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Coconut residue flour